The language forms of Instagram netizens’ rejection toward Rohingya immigrants in Aceh Province - Nuthihar, Rahmad; Ramli, Ramli; Rusli, Herman; Eliya, Ixsir; Menjamin, Sumaiyah (BAHASTRA, 2024)
The research examines the expressions of rejection used by Instagram users against Rohingya immigrants in Aceh Province. This study is grounded in the growing public apprehension surrounding the influx of Rohingya immigrants, which has been steadily rising over time. The current population of Rohingya immigrants in Indonesia is 1,600, since their initial arrival in Aceh in 2009. This instigates social and economic strife, in which the state of prosperity for the Acehnese population remains incomplete. The data source for this research is 500 comments from Instagram users on five posts on multiple Instagram media profiles. The research data was acquired in December 2023 and subsequently examined using a qualitative descriptive methodology. According to the study's findings, the most common form of rejection was one that used suggestions or other alternatives. It indicates that the individuals in Aceh exhibit a high degree of empathy; however, due to various conditions, they suggest alternative resolutions. Meanwhile, the most minimal form is rejection accompanied by gratitude. These findings demonstrate that Instagram users consider it unnecessary to use courteous language and consider it acceptable to reject Rohingya immigrants. This research also indicated that technological innovations have contributed to the advent of forms of language rejection. We have discovered novel types of rejection discourse, specifically employing symbols or emoticons, utilizing metaphors, and employing hashtags to exert influence over fellow Instagram users.